Enhancing Cognition in the Intellectually Intact - Whitehouse, Peter J. (The Hastings Center report, 1997)
As science learns more about how the brain works, and fails to work, the possibility for developing “cognition enhancers” becomes more plausible. And the demand for drugs that can help us think faster, remember more, and focus more keenly has already been demonstrated by the market success of drugs like Ritalin, which tames the attention span, and Prozac, which ups the competitive edge. The new drug Aricept, which improves memory, most likely will join them. Whether such drugs are good for individuals, or for society, is an open question, one that demands far more public discussion.